The Quarterly Journal of Economics Volume 130 May 2015 Issue 2 - Front Cover (Quarterly Journal of Economics, 2015)
Journal Article The Quarterly Journal of Economics Volume 130 May 2015 Issue 2 - Front Cover Get access The Quarterly Journal of Economics, Volume 130, Issue 2, May 2015, Page i1, https://doi.org/10.1093/qje/qju045 Published: 22 April 2015